2013
DOI: 10.11113/jt.v65.2342
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Synthetic Silica on Ultrafiltration PSf Membrane

Abstract: This study investigates the effects of synthetic silica(SiO2)with different weight percentage concentrations on the morphology and performance of the polysulfone (PSf) and polyethelene glycol (PEG) based membrane ultrafiltration (UF). Phase inversion method was used to prepare PSf/PEG ultrafiltration (UF) flatsheet membrane. SiO2 and N-Methyl 2 Pyrrolidone (NMP) were used as an additive and solvent respectively. The fabricated membrane was characterized by scanning electron microscope (SEM), X-ray diffraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…All the composite membrane exhibits the typical symmetric structure with sponge like structure. In the finding of [70], extensive diffusion caused by hydrogen bonding of the non-solvent with membrane functional group as well as hydrophilic properties of PEI has changed the membrane structure to sponge-like formation [74]. The second region as illustrated in Figure 3 shows the porous layer of the membrane.…”
Section: Results and Discussion Ftir Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…All the composite membrane exhibits the typical symmetric structure with sponge like structure. In the finding of [70], extensive diffusion caused by hydrogen bonding of the non-solvent with membrane functional group as well as hydrophilic properties of PEI has changed the membrane structure to sponge-like formation [74]. The second region as illustrated in Figure 3 shows the porous layer of the membrane.…”
Section: Results and Discussion Ftir Analysismentioning
confidence: 99%
“…Besides, it also exhibits good thermal stability. Thus, several works has been proposed to modified polysulfone membrane with aim to reduce the tendency of membrane foulants as well as improving other properties [70]. These studies involve on the addition of additive, composition formulation, processing variables as well as the study of kinetic and thermodynamic phase inversion.…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the obtained membranes is governed by the physical and chemical properties of the nanoparticles, polymer matrix, and method of nanoparticle incorporation. [2][3][4][5] One of the most common materials used in the preparation of polymer and nanocomposite membranes is polysulfone (PSF), which forms porous asymmetric structures, characterized by good mechanical, thermal, and chemical stability. 2,3 In recent years, in order to modulate PSF properties and match these to certain application different combinations of filler/PSF were proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Adding TiO 2 or SiO 2 to PSF showed an increase of skin layer thickness of the membrane and suppressed macrovoids formation while adding zirconium dioxide induced higher surface porosity. [4][5][6] Carbonaceous fillers were also used to prepare nanocomposite membranes. 7,8 PSF was embedded with multiwall carbon nanotubes 7 or graphene oxide (GO).…”
Section: Introductionmentioning
confidence: 99%
“…Also, Jin et al 33 found that silica nanoparticles enhanced thermal resistance, hydrophilicity, and flux of the ultrafiltration membranes. Harun et al 34 investigated the effect of synthetic silica with different concentrations on the morphology and performance of PSF membranes. By embedding 2 wt % of silica a high PWF and a high solute rejection were achieved simultaneously.…”
Section: Introductionmentioning
confidence: 99%